GENDERLECT AFFECTING ON POLITENESS STRATEGIES AND LANGUAGE - Arriyani, Nurfisi (English Community Journal, 2017)
Since language is a system of spoken sounds or conventional symbols for communicating thought, we use language to express our thoughts, feelings, ideas, etc to make a communication. We communicate to other people by using language. Therefore, the way we speak is influenced by the culture belonged to social group where we interact. Language reflects the context in which it is used. People use language differently in formal and casual context. Besides, people adapt their talk to suit their audience and talk differently to children, friends, customers and colleagues. The linguisticsÃ¢â¬â¢ form will also be affected by the purpose of peopleÃ¢â¬â¢s talk. They use variety of ways to express the Ã¢â¬ËsameÃ¢â¬â¢ message. Thus, this small project was done by interviewing two friends who had ever stayed abroad before, male and female (appendix) to see whether both of them use different politeness strategy in speaking English. They are coming from different origin, thus, the writer also wanted to see whether their L1 and their culture influence ways of their speaking. It is stated on Politeness theory that gender plays more prominently in the field of politeness but politeness theory has ignored the fact that based on gender, women and men will also perform politeness differently and it was proved in this small project. The writer interviewed two interviewees, male and female, by asking them to answer three questions prepared by the writer. The conversation was recorded and the writer analyzed the ways of their speech by listening to the recording. The writer found that both of them did not use any certain politeness strategies. The female friend talked more confident, were better in grammar and did not use more fillers or hedges. Vice versa, the male friend talked nicely, made many mistakes in grammar and use many fillers or hedges.